(untitled) (Indian Journal of Hill Farming, 2022)
The effect of two hosts and different colours of trichocard on the parasitising efficiency of Trichogramma pretiosum and T. japonicum was studied at the lab setting of 28 ± 2° C temperature and 75 ± 5 % relative humidity. In the present investigation, different biological parameters of T. pretiosum and T. japonicum reared on factitious hosts (Corcyra cephalonica and Galleria mellonella) were evaluated. The results revealed significant parasitisation of T. pretiosum on both hosts with 85.33 % (C. cephalonica) and 72.67 % (G. mellonella) parasitisation, respectively. The per cent parasitisation of T. japonicum on G. mellonella eggs was found to be significantly higher i.e., 72.33 % as compared to 60.67 % on C. cephalonica. Parasitoids reared on these two factitious hosts were used for checking the ovipositional preference of T. pretiosum and T. japonicum on different colours of trichocard. White, blue, yellow, purple, green, and red were the colours tested. The results showed that trichocards of white and green colour are better for mass production of Trichogramma spp.